2021
DOI: 10.1186/s13045-021-01101-6
|View full text |Cite
|
Sign up to set email alerts
|

CAR-T therapy alters synthesis of platelet-activating factor in multiple myeloma patients

Abstract: The chimera antigen receptor (CAR) T cell therapy is a novel and potential targeted therapy and has achieved satisfactory efficacy in patients with relapsed or refractory multiple myeloma (MM) in recent years. However, cytokine release syndrome (CRS) and clinical efficacy have become the major obstacles which limit the application of CAR-T in clinics. To explore the potential biomarkers in plasma for evaluating CRS and clinical efficacy, we performed metabolomic and lipidomic profiling of plasma samples from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The serum samples from all subjects were collected and stored in a digital-alarm-controlled freezer at − 80 °C until required for analysis. Sample preparation for the untargeted metabolomics analysis was performed as described in a previous study [ 26 ]. The Thermo Scientific ™ Vanquish ™ Horizon UHPLC system coupled to a Thermo Scientific ™ Q Exactive hybrid quadrupole-Orbitrap mass spectrometer (Thermo Fisher Scientific, Inc., Waltham, MA, USA) operated in full scan mode was used for the untargeted analysis of serum samples.…”
Section: Methodsmentioning
confidence: 99%
“…The serum samples from all subjects were collected and stored in a digital-alarm-controlled freezer at − 80 °C until required for analysis. Sample preparation for the untargeted metabolomics analysis was performed as described in a previous study [ 26 ]. The Thermo Scientific ™ Vanquish ™ Horizon UHPLC system coupled to a Thermo Scientific ™ Q Exactive hybrid quadrupole-Orbitrap mass spectrometer (Thermo Fisher Scientific, Inc., Waltham, MA, USA) operated in full scan mode was used for the untargeted analysis of serum samples.…”
Section: Methodsmentioning
confidence: 99%
“…Our group is dedicated to the discovery of novel therapeutic targets in MM. As previously reported, we found that targeting platelet-activating factor (PAF) remodeling might be a promising strategy to enhance MM CAR-T therapy [ 30 ]. In present study, our findings further disclose that CD229 regulates MM cell proliferation through the RAS/ERK pathway and CD229 can be considered as a promising target in diagnosis and treatment of MM.…”
Section: Discussionmentioning
confidence: 99%
“…The auto-sampler was conditioned at 4°C. Untargeted metabolomics were detected as described in a previous study ( 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…In 2003, Velcade (bortezomib for injection) was approved by the US Food and Drug Administration for the treatment of relapsed/refractory MM as the first proteasome inhibitor (5). The latest clinical MM therapy is a new immunomodulatory therapy using chimeric antigen receptor T cells, bispecific T cell conjugates, and immune checkpoint inhibitors (6). Although the therapeutic armamentarium for MM has continued to evolve (7)(8)(9)(10)(11)(12)(13)(14), MM still possesses the characteristics of high relapse and incurability.…”
Section: Introductionmentioning
confidence: 99%